(untitled) (Research, Society and Development, 2024)
The excellent performance of the semi-arid Northeastern vineyards since 1980s has established the São Francisco Valley as a major producer of grapes and fine wines under irrigated conditions. Several management practices are performed to overcome biotic and abiotic adversities, and among them the use of algae extracts. The objective of the work is to evaluate the effects of the commercial product Lithothamnium on the development, production and post harvest quality of BRS Vitória grapes produced in the São Francisco Valley. The orchard system was a trellis type with a single arm, where the BRS Vitória canopy was grafted onto the IAC-313 (Tropical) rootstock. The applications of Lithothamnium were made at 18, 23, 28, 33, 40, 47, 54, 77 days after pruning. The experimental design was a complete randomized block design with two factorial (Form of application x dose), with two forms of application Soil / Foliar and Soil and five doses 0, 5, 10, 15 and 20 kg / ha / cycle of Lithothamnium, with four blocks and two plants per block. The doses of 18 and 35 kg / ha / cycle application increased yield. Regarding fruit chemical characteristics, brix and the acidity did not differ. The application of doses 15 and 20 Kg / ha / Cycle were sufficient to improve agronomic characteristics as buds real fertility, berries length, diameter and weight, and yield of grapevine cv BRS Vitória.